The Ability of Students in Identifying Regular and Irregular Verb in English Text at the Eleventh Grade Student’s of SMA Kristen Rantepao - Antonius Lolopayung; Kansia Pitoy; Ilham Ilham (Universitas Khairun, 2023)
In order to achieve this goal the authors use a quantitative method. The population of this study was the eleventh grade students of SMA Kristen Rantepao. The total number of eleventh graders is 5 classes. In finding a sample, the writers use cluster sampling, where the writer only take some individuals who are part of the population. The writer chose class XI.1 as a sample consisting of 20 students as respondents. In collecting data, the writer uses written test. The results of the analysis show that the ability of eleventh graders at SMA Kristen Rantepao in identifying regular and irregular verbs in the text is classified as low, where students get an average score of 21.75%. The classification of students’ scores that have been presented shows that there are no students who get very good scores, there are 9(45%) students get good scores, there are 2 (10%) students get good scores, there are 5(25%) students get a poor scores and there are 4 (20%) students get a very poor score. Based on the results above, the writer concludes that the ability of eighth graders (VIII) SMA Kristen Rantepao in identifying regular and irregular verbs in the text is still poor, it can be seen from the average score of 21.25%.